The Influence Of The Work Environment And Career Development On Employee Performance With Job Satisfaction As An Intervening Variable In PT. PLN (Persero) ULP Muara Labuh In South Solok - Agustin, Rahma Putri; Dharma, Robby; Indriyenni (Journal of Science Education and Management Business, 2024)
PT. PLN (PERSERO) ULP Muara Labuh in South Solok, West Sumatra is one of the state-owned enterprises (BUMN) engaged in electricity. The purpose of this study is to determine and analyze the Effect of Work Environment and Career Development on Employee Performance with Job Satisfaction as an Intervening Variable. The research method used was quantitative research, with a sample of 58 respondents. In this study using SEM analysis tools using SmartPLS 3. The results showed that directly the most dominant variable, namely Career Development, had a positive and significant effect on Job Satisfaction, as evidenced by the company having various good career development programs so that it could affect employee job satisfaction in carrying out their duties. And Job Satisfaction has a positive and significant effect on Employee Performance, as evidenced by employees who already feel safe and comfortable at work. Where the better the Job Satisfaction, it will have an impact on improving the Performance of these Employees. While indirect testing for the most dominant variables states that Career Development has a positive and significant effect on Employee Performance through Job Satisfaction.